ALGEBRAIC THINKING ABILITY AND LEARNING INTEREST THROUGH SOCIAL MEDIA-BASED PICTORIAL PUZZLE IN NEW NORMAL ERA - Putik Rustika; Titi Rohaeti (MaPan : Jurnal Matematika dan Pembelajaran, 2020)
Algebraic ability is one of the most important abilities to be developed because it becomes the basis to achieve other mathematical thinking ability. In new normal era, information through social media is the main thing for society, particularly for children of the current generation. This study aims to describe algebraic thinking ability and students' interest in learning through social media-based pictorial puzzles. The method of the research is descriptive quantitative. The samples of this study were 6 students of grade VIII SMP Edu Global School in Cirebon city. This study indicates that algebraic thinking ability and students' interest in learning algebra are still classified as moderate and have not reached the high category, so it needs to be improved in the learning process.